The Habit of Using Hot Water Increasing Skin pH in Non-Atopic Dermatitis - Sylvia Anggraeni; Damayanti; Menul Ayu Umborowati; Asmahan Farah Adiba; Cita Rosita Sigit Prakoeswa (Faculty of Medicine, Universitas Airlangga, 2026)
Background: Skin health is influenced by hydration, pH balance, and environmental exposures. The skin’s barrier protects against irritants, pathogens, and moisture loss, while pH imbalances can lead to dryness, irritation, and inflammation. Research on atopic dermatitis is comprehensive, but little is known about how daily habits affect skin acidity in individuals without atopic conditions. Understanding these factors is key to improving skincare recommendations. Purpose: This study investigates the relationship between skin pH and personal habits such as handwashing, soap type, hot water use, chemical exposure, and air conditioning. By identifying influencing factors, this study arranges comprehensions into how daily routines impact skin health. Methods: A cross-sectional study was conducted with 37 non-atopic individuals (18–60 years) at Universitas Airlangga, Faculty of Medicine. Skin pH was measured on the left forearm using a Courage-Khazaka® pH meter. Data were analyzed using SPSS 26.0 with independent t-test. Ethical approval was granted (296/EC/KEPK/FKUA/2023). Result: Older individuals had higher skin pH (6.28±0.48). Mean pH was 6.19±0.48 in females and 6.13±0.89 in males. Dry skin and frequent hot water use significantly increased skin pH (p<0.05), while other factors showed no significant differences. Conclusion: Skin pH rises with age, potentially impairing barrier function. Sex differences may be hormone-related. Hot water use increases skin pH and dryness. Maintaining an acidic pH is essential for skin health, warranting further research into long-term effects.